2020
DOI: 10.1109/access.2020.2991014
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Hardware Prototyping Technologies as Tools for Learning

Abstract: Integrating hardware prototyping platforms such as Arduino, Raspberry Pi or BeagleBone Board in education is becoming more prevalent as the number of courses utilizing such platforms is continuously increasing. In this work, we conduct an analytical investigation on the plurality of courses that utilize or integrate hardware prototyping platforms. We examine curriculum and instructional material (e.g. course syllabi or outlines) through publicly available web informational resources (e.g. search engines). We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…[37], [38], [39], [40] Likewise, social networks can be used as a learning platform, for example, the use of a social network such as Facebook Gaming (FBG) was a change very accepted by students since it is not only a known platform but also allows live interaction, changing the approach to the use of social networks [28], similarly, mobile technology helped to enhance academic performance in different educational institutions in the world, being a learning tool that improves skills and academic results; such as the development of the IMELS Android application, using MySql and the Java programming language, added to this the implementation of Moodle (web learning platform) [20], thus allowing free access at any time and place, see Figure 11. It is demonstrated that its implementation contributes to inclusive education through a specific game for children with dyslexia called FORDYS-VAR [13] Figure 12 although it is in the beta phase, detecting errors to solve them, and children with dyslexia has no complications in understanding the game, they managed to obtain an influence and understanding of the high impact on these children.…”
Section: Gamesmentioning
confidence: 99%
See 2 more Smart Citations
“…[37], [38], [39], [40] Likewise, social networks can be used as a learning platform, for example, the use of a social network such as Facebook Gaming (FBG) was a change very accepted by students since it is not only a known platform but also allows live interaction, changing the approach to the use of social networks [28], similarly, mobile technology helped to enhance academic performance in different educational institutions in the world, being a learning tool that improves skills and academic results; such as the development of the IMELS Android application, using MySql and the Java programming language, added to this the implementation of Moodle (web learning platform) [20], thus allowing free access at any time and place, see Figure 11. It is demonstrated that its implementation contributes to inclusive education through a specific game for children with dyslexia called FORDYS-VAR [13] Figure 12 although it is in the beta phase, detecting errors to solve them, and children with dyslexia has no complications in understanding the game, they managed to obtain an influence and understanding of the high impact on these children.…”
Section: Gamesmentioning
confidence: 99%
“…[37], [60], [38], [39], [61], [40] There is evidence of a greater number of investigations in the incorporation of ICT, through virtual sessions on different platforms, as well as the use of pedagogical tools such as Google Classroom, Edmodo, Padlet, Popplet, and Kahoo, among others. Followed by the development of mobile applications with augmented reality, for the teaching of biology, astronomy, geometry, languages, etc.…”
Section: Gamesmentioning
confidence: 99%
See 1 more Smart Citation
“…are being employed as enabling tools in the prototyping process of IoT devices, given its versatility, peripheral integration structure, among others features [2]. These platforms also act as essential educational tools for the practical development of applications by students, who take advantage of these tools' computational and hardware capabilities to prototype their solutions, that may integrate different sensors, actuators, and other peripherals [3].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lockdown caused by the pandemic in 2020, the need for a digital transformation in all aspects of society arose. In the educational field, many educational institutions opted for the use of emerging technologies for teaching practice [6]. That is why mobile learning, as an emerging technology, has become an important tool in the teaching-learning process.…”
Section: Introductionmentioning
confidence: 99%